Determining the rate of underrecognition of West Nile virus neurologic disease in the province of Quebec in 2012. Issue 5 (16th March 2017) - Delage, Gilles; Dubuc, Sophie; Grégoire, Yves; Lowe, Anne‐Marie; Bernier, France; Germain, Marc
Abstract : BACKGROUND: During a major outbreak of West Nile virus (WNV) infection in the province of Quebec in 2012, public health authorities (PHAs) suspected underrecognition of West Nile neurologic disease (WNND). With data on acute infections detected in blood donors, an estimate of the degree of underrecognition was produced. STUDY DESIGN AND METHODS: All 2012 donors were tested for WNV infection with the use of reverse transcription–polymerase chain reaction (RT‐PCR). With the number of cases detected, the number of donors tested, our estimate of the duration of viremia, an estimate of the population at risk, and the ratio of WNND to total cases, an expected number of WNND cases was calculated. A Monte Carlo simulation was used to estimate the range of several of these variables. RESULTS: Seventeen RT‐PCR–positive donors were found among 52, 309 donations tested. In the base case, the total number of cases was 16, 095 and the expected number of WNND cases was 115. In the Monte Carlo simulation, the mean number of expected WNND cases was 136, and the median was 129. Since only 85 cases were reported to PHAs, it is estimated that between 26 and 37.5% of cases occurring in the province went undetected. CONCLUSION: The observation that close to one‐third of cases of WNND went undetected because of the omission of appropriate laboratory testing indicates the need for improvement in the investigation of acute neurologic syndrome of suspected infectious etiology in Québec.